SPRINKLER WATERING SYSTEM - REDDY, G.KARTHIK; BABU, P.MAHESH; KIRAN, K.RAVI; SHAIK, IRFAN (The journal of contemporary issues in business and government, 2022)
Irrigation is the basic need for the growth of the crops. The crops on one side are very fragile in nature, which can be easily taken care by providing exactly right amount of water for their growth. If the water is applied in abundant quantity then it will effect directly to the crop yield. And on the other side the weather of our country is not supporting in providing right amount of water to the crops as and when required due to the unpredictable nature of the climate change. In order to overcome the above situation we design an system named “SPRINKLER WATERING SYSTEM” which is useful for farming. By this we can reduce the watering cost to the farmers, maintenance cost. We can easily water the field each and every end. There will be some fields at higher areas at which it is difficult to water with the pipeline system. In that areas this Sprinkler Watering System is the best proposed solution to water the field. By this we can change the irrigation acre age (area of land which used for agriculture). Comparative irrigation crops yields, Labour savings, Production costs. Even can be used for spraying peticides.It will definitely reduce the capital cost, maintenance cost with better efficiency.The sprinkler watering system is better investment in long run as compared to surface methods. As sprinkler irrigation proved to be better in uniform distribution of water, uniform application of fertilizers and water saving especially in water scarcity. With this it is easy to irrigate the field at each and every end by rotating the sprinkler itself.